2019
DOI: 10.18388/abp.2019_2804
|View full text |Cite
|
Sign up to set email alerts
|

Cold-modulated small proteins abundance in winter triticale (x Triticosecale, Wittm.) seedlings tolerant to the pink snow mould (Microdochium nivale, Samuels & Hallett) infection

Abstract: Two winter triticale (x Triticosecale Wittmack) model cultivars: Hewo (tolerant to pink snow mould) and Magnat (sensitive) were used to test the effect of cold-hardening (4 weeks at 4°C) on soluble ≤50 kDa protein profiles of the seedling leaves. The presence and abundance of individual proteins were analysed via two-dimensional gel electrophoresis (2-DE) and Surface-Enhanced Laser Desorption/Ionization Time-of-Flight (SELDI-TOF). Up to now, no proteomics analysis of triticale response to hardening has been pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Low temperature (4 weeks at 4 °C) may increase the tolerance of triticale seedlings to stresses coexisting with cold in winter, which may persistently follow throughout the early spring period and even in the adult phase of the plant [ 16 , 23 , 28 , 32 , 51 , 52 ]. Tolerance to pink snow mold caused by M. nivale appears after a period of hardening with low temperature and is a genotype-dependent, complex feature significant for wintering seedlings [ 23 , 31 , 32 , 52 , 53 ]. Furthermore, Dyda et al [ 31 ] presented new insights into the mechanism of triticale resistance to M. nivale .…”
Section: Fungal Infection Tolerance After Cold-acclimationmentioning
confidence: 99%
See 3 more Smart Citations
“…Low temperature (4 weeks at 4 °C) may increase the tolerance of triticale seedlings to stresses coexisting with cold in winter, which may persistently follow throughout the early spring period and even in the adult phase of the plant [ 16 , 23 , 28 , 32 , 51 , 52 ]. Tolerance to pink snow mold caused by M. nivale appears after a period of hardening with low temperature and is a genotype-dependent, complex feature significant for wintering seedlings [ 23 , 31 , 32 , 52 , 53 ]. Furthermore, Dyda et al [ 31 ] presented new insights into the mechanism of triticale resistance to M. nivale .…”
Section: Fungal Infection Tolerance After Cold-acclimationmentioning
confidence: 99%
“…The proteomic profiling allowed for the identification of candidate proteins associated with the cold acclimation of triticale seedlings [ 53 ] as well as the tolerance to freezing and pink mold infection [ 52 ]. The content of individual proteins was analyzed by two-dimensional gel electrophoresis (2-DE) and matrix-enhanced time-of-flight laser desorption/ionization (SELDI-TOF).…”
Section: Fungal Infection Tolerance After Cold-acclimationmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential role in defensive response to M. nivale infection was proposed for catalase, peroxidase, and thiolspecific antioxidant proteins (Gołebiowska-Pikania and Golemiec 2015) in winter triticale. Recently, Gołebiowska et al (2019) concluded that genotype and cold treatment significantly affected the amount of small proteins in winter triticale leaves. The pattern of these proteins could be correlated with the level of the resistance to pink snow mold infection.…”
Section: Candidate Genes and Genomics Of Host Resistancementioning
confidence: 99%